Analisis Pembelajaran Daring Dengan Aplikasi Whatsapp Siswa Kelas Ii Sekolah Dasar Persatuan Ummat Islam Haurgeulis Indramayu - Udin, Udin; Rahim, Abdur; Fitri, Ahmad Asrof (Lembaga Penelitian dan Pendidikan Mandala, 2023)
The year 2020 has been a tough year for all of us, until now Indonesia is still hit by the Covid-19 pandemic. Bringing impact on the implementation of education in Indonesia. One of them is the online or online learning policy for all students to students due to social restrictions. This study aims to analyze and then describe; (1) The practice of online learning using the WhatsApp application for second grade students of SD PUI Haurgeulis Indramayu (2) The advantages and disadvantages of online learning using the WhatsApp application. This research is a qualitative research with an inductive approach. Informants in this study were teachers, parents and students. Methods of data collection is done by using interviews, observation and documentation. The results of the study show that, (1) The implementation of online learning for class II C students at SD PUI Haurgeulis Indramayu is good with the concept of learning is carried out via cellphones or cellphones with the WhatsApp application. In online learning the teacher always makes online lesson plans with references from the internet and discusses with other teachers (2) The advantage of online learning is that teachers become more creative and able to use electronic media in learning. Meanwhile, the lack of online learning is that students cannot easily understand the learning material presented, because each student is quick to grasp and slow to understand the material.